Connectivism Theory in Safety and Health Education in Classical Universities - Gvozdii, Svitlana; Litvinova, Anastasiia; Tymchenko, Ganna (Educological discourse, 2023)
Planet Earth, humanity in general and the education system in particular, in the first quarter of the XXI century have faced a large number of problems and situations that require regulation. The use of modern technologies based on connectivism theory in the study of health and safety issues within classical (non-medical) higher education institutions in Ukraine is relevant. The aim of the article was to test the effectiveness of using online learning, e-learning, as well as open educational resources, distance learning technologies based on connectivism theory in teaching health and safety issues in classical universities. The Internet has now become a huge collaborative learning space. In today’s dynamic theory of learning «connectivism», it is the Internet that has become the main link. Connectivism is a conceptual framework that sees learning as a networked phenomenon influenced by technology and socialisation and learning as a process of pattern recognition. Connectivism emphasises the need to consider, if possible, all the changes that took place yesterday in order to realise new knowledge today and in the future. In the context of safety and health, the need to learn from yesterday’s life experiences to ensure health and safety today and in the future becomes relevant. The article substantiates how connectivism theory can be used to explore issues of safety and health. Many forms of implementation of technologies combining e-learning and open educational services to build a blended learning system in higher education are provided. The first accessible and open educational resource (distance learning course) «My Health» was created to implement quality learning on safety and health issues. The course also uses technology to combine e-learning and open educational services of the educational platforms Coursera, Khanacademy, Canvas, Udemy and Eliademy. Studying health and safety issues based on connectivism theory was implemented using social media; the use of gamification techniques involved performing tasks and exercises and turning them into a competitive game to make learning more interactive. Sites with simulations of different processes engaged students in deep learning that promoted understanding, as opposed to superficial learning that required only memorization. A post-study survey of both full-time and part-time students showed an increase in academic achievement with the use of e-learning based on connectivism theory. At the same time, the authors draw attention to the need for offline work to build sustainable practical skills in safety and health. A promising direction remains the development of educational platforms and introduction of open educational services and E-learning in professional training of specialists in other fields of science, creation of high-quality open Ukrainian distance learning courses and services worthy of international level, as well as introduction of mass interactive courses on a modern open Internet platform.